Cycle reversions and dichromatic number in tournaments. (March 2019) - Ellis, Paul; Soukup, Dániel T.
Abstract: We show that if D is a tournament of arbitrary size then D can be made to have only finite strong components after reversing a locally finite sequence of cycles. In turn, we prove that the vertex set of any tournament can be covered by two acyclic induced subgraphs after reversing a locally finite sequence of cycles. This provides a partial solution to a conjecture of S. Thomassé.